Market Structure Analysis in Improving the Efficiency Of Company Operational Management: Manajemen - Rahmadani Rahmadani; Zefriyenni Zefriyenni (Jurnal Multidisiplin Sahombu, 2026)
Market structure is a crucial factor influencing the effectiveness of a company's business strategy and operational efficiency. The differing characteristics of each market structure lead companies to implement different operational strategies in managing production, marketing, distribution, and cost control. This study aims to analyze how market structure contributes to improving the efficiency of a company's operational management. The study used the Systematic Literature Review (SLR) method, reviewing various national and international scientific articles discussing market structure and operational management. The results show that companies that are able to align their operational strategies with the characteristics of the market structure will achieve cost efficiency, increased productivity, better service quality, and greater competitiveness. Conversely, operational strategies that do not align with market conditions lead to inefficiency and decreased company performance.